INFLUENCE OF TIME AND METHOD OF CULTURE ON THE PRODUCTION OF BROCCOLI IN TRANSYLVANIA PEDOCLIMATIC CONDITIONS - Laura Ardelean; Maria Apahidean; Al. I. Apahidean (Agricultura, 2013)
Broccoli is grown for hypertrophied inflorescences, less compact than those of cauliflower, which are used to prepare various dishes or for freezing. Value of broccoli inflorescences is high due to the rich content in carbohydrates, vitamins and minerals. Broccoli culture is practiced in open field and in protected areas. Transylvania climatic conditions are favorable for the cultivation of this species. Broccoli cultures are started with seedlings and this is leading to additional costs for their production. Experience was conducted in 2010-2011, in Reghin, Mures County. Experimental factors were time of planting and the culture method. Experimental culture was established at different times (April, May, June) by two methods (by planting seedlings and direct sowing).